A liberdade em “Sursis”: incursões sartrianas - Opalchuka, Josieli Aparecida (2019)
The present dissertation have a general scope of presenting the freedom conception and how human and world defines themselves from the problematic of freedom in the horizon of Sartre's phenomenological ontology allied, in turn, to his literary production under a very precise cut: the second tome of Sursis in the framework of the trilogy The Paths of Freedom. Therefore, the research seeks, at first moment, situate freedom as an inalienable project rooted in facticity. In a second moment, it is a question of understanding the intrinsic relationship, established in Sartrian work, between philosophy and literature. We judge that Sartre's literature contains within itself the capacity to describe the lived and, moreover, enables the description of all ambiguity and complexity of the human situation so well described in the light of the first philosophical masterpiece, Being and Nothingness. Nevertheless, is starting from this premise, that an implication it can be recognized between philosophy and literature. This alliance becomes even more visible in the third moment of the research, which goes to analyze the central problem posed by Sursis that contingency becomes the background from where the characters inscribe their history, their engagement, ultimately, their singular/concrete/universal experience in a panorama such as the interwar period. The research, then, advocates the thesis that Sursis embodies, in an exemplary way, the existential spirit of a truly rooted freedom, namely, absolutely engaged, incarnated in an inexorable temporality where the human situation really launches itself as a project.